'What does professional curiosity mean to you?': an exploration of professional curiosity in probation. (14th February 2021) - Phillips, Jake; Ainslie, Sam; Fowler, Andrew; Westaby, Chalen
Abstract: This article explores the concept of professional curiosity in relation to probation practice. We synthesise existing relevant literature to develop a theoretical framework of how professional curiosity is understood, arguing that professional curiosity can be used to manage risk, develop the therapeutic alliance, and facilitate knowledge building. We then present analysis of how the concept has been used in probation policy and analyse data generated in the first study of professional curiosity amongst probation workers in England and Wales. We conduct a content analysis of the meanings that probation staff ( n  = 445) attribute to the term professional curiosity by analysing responses to an open-ended question, which asked participants 'What does professional curiosity mean to you?'. Our analysis is exploratory in nature and sheds some light on how probation workers in England and Wales understand professional curiosity. Respondents were more likely to associate the term with managing risk, although there is considerable heterogeneity between the way it is understood. We draw on existing research about probation training, culture and values to explore the reasons for these findings. We conclude by considering the limitations of the research and highlighting policy implications.